Life cycle analysis of wheat and barley crops for bioethanol production in Spain. (7th June 2005) - Lechon, Y.; Cabal, H.; Saez, R.
A Life Cycle Assessment (LCA) of the agricultural production of wheat and barley grain to be used as a raw material for bioethanol production in Spain is performed. The objective of the work presented is to compare the environmental impact of the production of these two alternative raw materials for the production of bioethanol. This study is carried out in the frame of a higher scope study, a Life Cycle Analysis of alternative fuels for transport launched by the Spanish Ministry of Environment. Results show that wheat cultivation has a smaller impact in every impact category with the exception of the global warming category. Considering only the agricultural production stage, it seems that wheat is more recommendable than barley for bioethanol production, but given that the main objective in the biofuels introduction is the fulfilment of the greenhouse gases reduction commitments, barley is a better option than wheat.